Tmesiphantes mirim sp. nov. (Araneae: Theraphosidae) from the Atlantic Forest of Bahia, Brazil, biogeographical notes and identification keys for species of the genus - Willian Fabiano-da-Silva; José Paulo Leite Guadanucci; Márcio Bernardino DaSilva (Zoologia (Curitiba), 2015)
A new species of Tmesiphantes Simon, 1892 is described and illustrated, based on eight male specimens collected at the Una Biological Reserve, southern state of Bahia, Brazil. It is distinguished by the morphology of male palpal bulb and tibial apophysis. The new species is very small and is the smallest theraphosid described to date (body length 5.5 mm). It is distinguished from congeners by the size, which vary from 12 mm (T. riopretano) to 23.8 mm (T. nubilus) in other species of the genus, aspect of palpal bulb, sternal posterior sigillae close to sternal margin and by the aspect of tibial apophysis which lacks the prolateral branch. Tmesiphantes presently comprises nine species. Sixth have been described for the southern region of Bahia, a well known area of endemism in the Atlantic Forest. Identification keys for Tmesiphantes males and females are presented.